Penerapan Hukum Tindak Pidana Korupsi Dalam Perbankan - Siregar, Friska Anggi (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
Corruption in the banking industry is a severe problem that must be addressed appropriately. Due to the obstacles inherent to difficult-to-detect crimes and some theoretical and legal concerns of law enforcement, the application of criminal law against perpetrators of banking corruption is not yet at its maximum. Hence, there is a need to educate individuals not to engage in corrupt behavior, to strengthen the professionalism of law enforcement, and to implement nondiscriminatory sanctions. Some rules govern corruption and banking crimes, but existing regulations must be enhanced to solve some law enforcement loopholes. Thus, implementing criminal law against corruption offenses in banking becomes crucial for maintaining public confidence in the banking sector and promoting sustainable economic growth.